Improved executive function in patients with systemic lupus erythematosus following interactive digital training. (July 2022) - Kozora, Elizabeth; Zell, JoAnn L; Baraghoshi, David; Smith, Rebecca M; Strand, Matthew
Objective: This study aimed to evaluate the sensitivity of a digital platform to assess attentional and executive function in systemic lupus erythematosus (SLE) patients, and to evaluate the impact of an at-home interactive digital treatment to improve cognitive dysfunction in this clinical population. Background: Deficits in attention and executive function are common in patients with SLE. Despite these cognitive difficulties, there are limited brief assessment techniques and few treatment options to improve cognitive abilities in patients with SLE. Interactive digital treatment approaches (use of video game-based software) have been successful in identifying and improving cognition in other clinical populations. Methods: Sixty SLE patients completed baseline neuropsychological tests (of attention, psychomotor speed, and executive function), a tablet-based digital platform (EVO TM Monitor), and biobehavioral measures. The patients were randomized into treatment SLE ( n = 30) or no contact control SLE ( n = 30) groups, and returned 4 weeks later for follow-up cognitive, EVO Monitor, and biobehavioral testing. The SLE treatment group was trained on a tablet-based digital treatment (AKL-T01) and was instructed to complete 5 sessions at least 5 days per week for 4-weeks for a total of approximately 25 min of gameplay per day. Results: Systemic lupus erythematosus patients demonstrated impairment in visuomotor and processing speed, visual attention, and cognitive flexibility/sequencing skills at baseline. The video game-like treatment group (AKL-T01) had significant improvement in visuomotor speed (Trail Making A) and cognitive flexibility/sequencing (Trail Making B) compared to the control group at 4-week follow-up. The treatment group also demonstrated significant improvement in EVO Monitor multitasking at follow-up (with no change in controls). At baseline, a multitasking metric from EVO Monitor was associated with performance on tasks of cognitive flexibility (Trail Making B) and psychomotor speed (WAIS-IV Coding). Conclusions: These findings provide evidence that SLE patients who participated in a 4-week interactive digital video game-like activity had significant improvement in motor speed and executive functions, and would benefit from participation in digital interventions designed to target frontoparietal networks of the brain. Preliminary findings also suggest specific metrics from EVO Monitor may also be useful to detect cognitive impairment and cognitive changes in patients with SLE.